Safe and effective superoxide dismutase 1 silencing using artificial microRNA in macaques - Borel, Florie; Gernoux, Gwladys; Sun, Huaming; Stock, Rachel; Blackwood, Meghan; Brown, Jr, Robert H; Mueller, Christian (Science translational medicine, 2018)
Amyotrophic lateral sclerosis (ALS) is a fatal neurological disease caused by degeneration of motor neurons leading to rapidly progressive paralysis. About 10% of cases are caused by gain-of-function mutations that are transmitted as dominant traits. A potential therapy for these cases is to suppress the expression of the mutant gene. Here, we investigated silencing of , a gene commonly mutated in familial ALS, using an adeno-associated virus (AAV) encoding an artificial microRNA (miRNA) that targeted In a superoxide dismutase 1 (SOD1)-mediated mouse model of ALS, we have previously demonstrated that silencing delayed disease onset, increased survival time, and reduced muscle loss and motor and respiratory impairments. Here, we describe the preclinical characterization of this approach in cynomolgus macaques ( ) using an AAV serotype for delivery that has been shown to be safe in clinical trials. We optimized AAV delivery to the spinal cord by preimplantation of a catheter and placement of the subject with head down at 30° during intrathecal infusion. We compared different promoters for the expression of artificial miRNAs directed against mutant Results demonstrated efficient delivery and effective silencing of the gene in motor neurons. These results support the notion that gene therapy with an artificial miRNA targeting is safe and merits further development for the treatment of mutant -linked ALS.